Barriers to the adoption of sustainable construction materials in Zimbabwe - Moyo, Tirivavi; Mudombo, Mable Vongai; Omer, Mazen Mohamed Alkhdar; Moyo, Cynthia (Emerald Publishing Limited, 2024)
Purpose The built environment contributes to environmental concerns, including carbon emissions, with traditional construction materials being problematic. Adopting sustainable construction materials (SCMs) is envisaged; however, barriers exist. Hence, this study sought to determine significant barriers to adopting SCMs in Zimbabwe.